2013
DOI: 10.4103/2278-0203.110328
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different parameters for recording sagittal maxillo mandibular relation using natural head posture: A cephalometric study

Abstract: Background:Commonly used parameters for anteroposterior assessment of the jaw relationship includes several analyses such as ANB, NA-Pog, AB-NPog, Wits appraisal, Harvold's unit length difference, Beta angle. Considering the fact that there are several parameters (with different range and values) which account for sagittal relation, and still the published literature for comparisons and correlation of these measurements is scarce. Therefore, the objective of this study was to correlate these values in subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In the past, multiple researchers have correlated various cephalometric analyses for assessing anteroposterior jaw disrepancy. 14 - 18 Ahmed et al 19 reported the diagnostic accuracy of various cephalometric skeletal parameters for assessing the skeletal facial vertical pattern. However, to our knowledge, no such study has evaluated the reliability of anteroposterior skeletal dysplasia parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, multiple researchers have correlated various cephalometric analyses for assessing anteroposterior jaw disrepancy. 14 - 18 Ahmed et al 19 reported the diagnostic accuracy of various cephalometric skeletal parameters for assessing the skeletal facial vertical pattern. However, to our knowledge, no such study has evaluated the reliability of anteroposterior skeletal dysplasia parameters.…”
Section: Introductionmentioning
confidence: 99%
“…, 3 , 8 , 9 Riedel 2 introduced the ANB angle in 1952. It estimates the discrepancy of maxilla and mandible in reference to the anterior cranial base.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the diagnosis drawn from the most commonly used analyses is still questionable 2 3 , 8 , 9 , 10 In order to overcome these shortcomings, Kim and Vietas 11 studied cephalograms of 102 subjects with normal occlusion and 874 subjects with different dental malocclusions based on Angle's classification, and proposed the anteroposterior dysplasia indicator (APDI) which scores the sagittal skeletal relationship. The APDI is the sum of three interplaner angles that showed the highest correspondence with Angle's classification 12 …”
Section: Introductionmentioning
confidence: 99%
“…This comparative cross-sectional study was conducted at the Orthodontics Department of Armed forces Institute of Dentistry (AFID) Rawalpindi Pakistan from February to August 2019. The sample size was calculated by WHO sample size calculator using population proportion of sagittal maxillomandibular relation using natural head posture as 30%, 11 by keeping the margin of error as 10%. A consecutive sampling technique was used to gather the sample.…”
Section: Methodsmentioning
confidence: 99%